Game-based learning: An alternatif learning model in covid-19 distance learning - Puspita Ratna Susilawati; Luisa Diana Handoyo (Universitas Negeri Jakarta, 2022)
Distance learning as Covid-19 pandemic solution has student learning boredom as a negative impact. Game application can increase students' enthusiasm and motivation to learn in distance learning. The game-based learning (GBL) model is potentially applied to create a fun learning atmosphere and overcome learning boredom. This study aims to determine the effect of GBL implementation on cognitive learning outcomes and student responses in the biological interaction chapter in Covid-19 distance learning. This research wasexperimental research (one-group pretest-posttest design). The research sample was 25 students. This research used one treatment group without a control group. The test questions were used as cognitive learning outcomes instruments. The questionnaire was used as a student response instrument. Game application used were classified as mobile games, single-player games, role-playing game (RPG). GBL syntaxes were pre-experimentation, experimentation, reflection, activity, and discussion. The results showed that the implementation of GBL in the biological interaction chapter in Covid-19 distance learning affected students' cognitive learning outcomes. The effect of this model could improve students' cognitive learning outcomes with 28% students of low category N-gain while 72% students of medium and high.